Aries netwerk een constructicon - Reuneker, Alex; Boogaart, Ronny; Lensink, Saskia (Leiden University Press, 2016)
Columns presented to Arie Verhagen on September 30, 2016 on the occasion of his retirement as professor of Dutch Linguistics at Leiden University. Constructions - central to Arie's work - are conventionalized connections of form and meaning, which can vary greatly in their degree of abstraction. The entire continuum is represented in this collection: from petrified combinations in which all elements are fixed